Cryptic Temporal Bone Fibrous Dysplasia with Predominant Vestibular Symptoms: A Case Report - kenechukwu Uche-Okonkwo; Moses Ayodele Akinola; John Ifeanyi Nwadiokwu; Oluwapelumi Olusoga-Peters; Babatunde Akinola Bamgboye (Babcock University Medical Journal, 2025)
Background: Temporal bone fibrous dysplasia is relatively uncommon and typically manifests as a monostotic form of the disease. It often presents with noticeable temporal bone deformity, clinically appearing as a hard bony swelling behind or around the ear, external auditory canal stenosis, and conduction deafness. While symptoms such as aural fullness, tinnitus, and hearing loss are commonly reported, specific vestibular symptoms like vertigo and nystagmus are considerably less frequent.